2003
DOI: 10.1074/jbc.m302969200
|View full text |Cite
|
Sign up to set email alerts
|

Probing Lipid Mobility of Raft-exhibiting Model Membranes by Fluorescence Correlation Spectroscopy

Abstract: Confocal fluorescence microscopy and fluorescence correlation spectroscopy (FCS) have been employed to investigate the lipid spatial and dynamic organization in giant unilamellar vesicles (GUVs) prepared from ternary mixtures of dioleoyl-phosphatidylcholine/sphingomyelin/cholesterol. For a certain range of cholesterol concentration, formation of domains with raft-like properties was observed. Strikingly, the lipophilic probe 1,1-dioctadecyl-3,3,3,3-tetramethylindocarbocyanine perchlorate (DiI-C 18 ) was exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

71
457
6
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 477 publications
(538 citation statements)
references
References 53 publications
71
457
6
4
Order By: Relevance
“…We also find that glycan-patterned phase separation is thermally reversible -thus indicating that the effect is thermodynamic rather than kinetic -and that phase patterning results likely due to a preferential interaction of glycans with ordered lipid phases. These findings have implications for membrane-mediated transport processes [6][7][8] , potentially rationalize long-standing observations that differentiate the behaviour of native and model membranes [9][10][11][12][13] , and may indicate a more intimate coupling between cellular lipidomes and glycomes than realized currently.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…We also find that glycan-patterned phase separation is thermally reversible -thus indicating that the effect is thermodynamic rather than kinetic -and that phase patterning results likely due to a preferential interaction of glycans with ordered lipid phases. These findings have implications for membrane-mediated transport processes [6][7][8] , potentially rationalize long-standing observations that differentiate the behaviour of native and model membranes [9][10][11][12][13] , and may indicate a more intimate coupling between cellular lipidomes and glycomes than realized currently.…”
supporting
confidence: 69%
“…In general, diffusion of fluorescent probes is about 1-10 times slower in the Lo phase compared to the Ld phase due to the increased viscosity of the ordered phase 10 . Lipids are immobile in the So phase 10 .…”
Section: Fluorescence Recovery After Photobleaching (Frap) Measuremenmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, reducing membrane fluidity by addition of cholesterol reduced the diffusion coefficients of lipid and protein to the same degree. Thus, streptavidin or agonist binding has, if at all, only a small effect on mobility, which can be explained by the negligible hydrodynamic drag introduced by the protruding protein domains in the aqueous phase [26,39].…”
Section: Discussionmentioning
confidence: 99%
“…21) Recently, Sieben et al 22) found that pre-incubation for 24 h with the saponin compound R-hed-erin could inhibit the terbutaline-stimulated internalization of the b 2 AR, which is in agreement with the fact that saponins are cholesterol-complexing agents and that cholesterol depletion is known to inhibit receptor internalization. [23][24][25][26] Chemically, glycyrrhizin is a triterpenoid saponin glycoside, therefore, we hypothesized that glycyrrhizin may have a positive effect on the regulation of b 2 AR agonist-induced internalization of b 2 ARs.…”
mentioning
confidence: 99%